(untitled) (CIPEEX, 2025)
The issue of stray animals is a global concern, with over 200 million animals living on the streets worldwide. In Brazil alone, approximately 30 million animals are facing such extreme vulnerability, including cruelty, malnutrition, and disease. This problem not only jeopardizes the well-being of these animals but also poses a significant public health risk, as around 60% of human diseases are zoonoses, transmitted from animals to people. To address this serious situation, the NPET Project is being developed with the goal of improving the living conditions of abandoned animals, aligning with the United Nations’ Sustainable Development Goals (SDGs) 15 and 3. SDG 15 aims to protect terrestrial life, while SDG 3 promotes health and well-being. NPET seeks to support shelters and NGOs dedicated to caring for vulnerable animals through the collection of physical and financial donations, as well as community engagement. Additionally, improving the living conditions of animals can help reduce the spread of zoonoses (diseases transmitted between humans and animals): controlling these conditions can significantly lower the incidence of related deaths, promoting population well-being. The main product of NPET is an innovative digital platform that connects donors with animal shelters and protection NGOs. Through geolocation tools, users can locate nearby shelters and popular veterinary clinics, and make donations to these institutions. Donations can be either monetary or in the form of physical items, such as food, medicine, and other necessary supplies. Once a donation is made, the platform ensures transparency by informing donors about how their contributions are being used to help the animals. In the future, NPET also plans to expand its platform by adding an adoption system. Through this system, NGOs will be able to register detailed information about the animals available for adoption, including their name, breed, age, whether they are neutered or not, and a brief description of their behavior. The goal is to make it easier to adopt these animals, helping to promote them and reduce the time they spend waiting for a loving home. The key differentiator of NPET is its pioneering and integrated approach. In the current landscape, there is no nationally recognized software that offers such a practical, efficient, interactive, transparent, and accessible solution to support the cause of stray animals. Therefore, the project stands out for its innovation in this area, bringing a solution that combines technology and social responsibility to address an urgent and often overlooked problem in today’s society.